The structure of the integral fixture design system - Rodić, Milorad (Journal of Production Engineering, 1993)
This paper initially examines the factors influencing the fixture design process. Building upon this analysis, a fixture design information model is formulated. The model implies and mandates a comprehensive approach to fixture design. The paper goes on to depict the established structure of the comprehensive fixture design system, which is organized across three levels: fixture selection, fixture design, and the definition of design documentation. The initial step involves the selection of existing fixtures, which may vary in terms of their operational readiness. The subsequent step encompasses the design of new fixtures or the incorporation of adjustments and modifications to existing fixtures to accommodate new machining operations.